The Role Of Al-Hidaya By Burhanuddin Al-Marghinani In The Science Of Hilyaf - Gadzhiev Mavlidin Gadzhievich (Indonesian Journal Publisher, 2025)
The article describes “Al-Hidaya” (The Guidance), authored by Burhanuddin al-Marghinani in the 12th century, which is a seminal work in Islamic jurisprudence, particularly within the Hanafi school of thought. This comprehensive legal text has significantly influenced the science of hilyaf, which studies legal disagreements among various Islamic scholars and schools of thought (mazhabs). This article explores the impact of